Superalloys 2008 (Eleventh International Symposium) 2008
DOI: 10.7449/2008/superalloys_2008_609_618
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxidation and Hot Corrosion in a Nickel Disc Alloy

Abstract: This paper describes work to study oxidation and hot corrosion damage in nickel disc alloy RR1000. Oxidation damage has been characterised via mass change data from thermogravimetric analyses at temperatures from 700 to 800 ºC and cyclic oxidation testing at 700 and 750 ºC. Thin oxide scales rich in Cr and Ti have been found to grow in a parabolic dependence with time. Oxidation rate constants have been correlated with temperature using an Arrhenius equation. Through the use of simplifying assumptions, mass ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 9 publications
(15 reference statements)
3
70
0
Order By: Relevance
“…[10][11][12][13][14] Energy-dispersive x-ray analyses showed that the overall oxide morphology from the external scale to internal oxides of Cr 2 O 3 /TiO 2 in the outer scale to Al 2 O 3 internally agrees with the expected thermodynamic behavior; however, and in contrast to the thermodynamic predictions, the alloy formed an outer layer of TiO 2 , believed to be at the expense of its oxidation resistance. 14,15 Cationic diffusion is inferred from the known transport mechanisms for Cr 2 O 3 growth 16,17 and from the fact that titanium must diffuse outwards to form above the outer scale.…”
Section: Classic Oxidationmentioning
confidence: 50%
“…[10][11][12][13][14] Energy-dispersive x-ray analyses showed that the overall oxide morphology from the external scale to internal oxides of Cr 2 O 3 /TiO 2 in the outer scale to Al 2 O 3 internally agrees with the expected thermodynamic behavior; however, and in contrast to the thermodynamic predictions, the alloy formed an outer layer of TiO 2 , believed to be at the expense of its oxidation resistance. 14,15 Cationic diffusion is inferred from the known transport mechanisms for Cr 2 O 3 growth 16,17 and from the fact that titanium must diffuse outwards to form above the outer scale.…”
Section: Classic Oxidationmentioning
confidence: 50%
“…The current specimens received test exposures of 650 • C under minimum dwell fatigue for only 22 to 74 hours. Measurements from FIB analyses showed minimum dwell oxidation damage was of a similar magnitude to stress-free isothermal measurements quoted by Encinas-Oropesa et al after a more onerous 200 hour exposure at 700 • C [5].…”
Section: Discussionmentioning
confidence: 52%
“…Given the fact that oxidation kinetics for nickel alloys at 650C is extremely slow [25], there is insufficient time for oxide formation to happen ahead of the crack tip within the order of seconds. Direct observations of internal oxidation and associated damage were only available on smooth specimens, which have been exposed to oxidizing environment for a considerably long time, mostly greater than 20 hours [2,12,13,26]. The current work also showed that crack growth rates in air at high-temperature can be predicted well from the dynamic embrittlement hypothesis, though collecting experimental evidence of crack tip oxygen diffusion process and measurements of oxygen concentration near the crack tip are challenging tasks and yet to be accomplished.…”
Section: Discussionmentioning
confidence: 71%
“…and κ 0 are the oxygen diffusivity and mobility at 650°C and assumed to be independent of the oxygen concentration. In the present work, no attempt was made to model chemical reaction kinetics, vacancy formation or the transport of other species [26] other than oxygen diffusion near the crack tip.…”
Section: Deformation-assisted Oxygen Diffusionmentioning
confidence: 99%
See 1 more Smart Citation